Regulation, red tape and location choices of top R&D investors - Daria Ciriaci; Nicola Grassano; Antonio Vezzani (European Commission, Joint Research Centre (JRC), 2016)
This paper investigates how product and labour market regulations and red tape affect the way in which top corporate research and development (R&D) investors worldwide organise their cross-border operations. The decision about where a company locates its international subsidiaries is modelled using location-specific framework conditions, socio-economic factors and other controls commonly used in the economic geography literature. The location decision drivers are estimated using a multilevel mixed-effects logistic regression, controlling for both fixed and random effects. Our results confirm that both product market regulation (PMR) and employment protection legislation (EPL) significantly affect the location decisions of top R&D investors, as well as red tape and profit tax. The marginal effect of PMR is by far the largest, followed by EPL; the cost of starting a business and profit tax show lower marginal effects. Moreover, we found that (i) PMR and EPL are complementary (i.e. reducing one would also reduce the negative impact of the other) and (ii) of the three components of the PMR indicator —barriers to trade and investment, state control and barriers to entrepreneurship—the latter is the one with the lowest marginal effect. Policy implications are drawn accordingly.
Keywords: F23; D22; L20; 330; Multinational Corporations (MNCs); Internationalization; Product market regulation; Employment protection.